Improved procedures for production and purification of 135La from enriched [135Ba]BaCO3 on a 16.5 MeV cyclotron. (February 2023) - Pedersen, Kristina Søborg; Deville, Claire; Søndergaard, Ursula; Jensen, Mikael; Jensen, Andreas I.
Abstract: Lanthanum-135 ( 135 La) is a favorable Auger electron emitter with a high Auger electron yield and low gamma emission, making it promising for Auger electron radiotherapy. However, successful application requires reliable and scalable 135 La production. Up to now, metallic natural barium ( nat Ba) is a commonly used target material, but this material is sensitive to moisture and oxidation. BaCO3 has also been tested, due to its higher chemical stability. However, BaCO3 has poor thermal conductivity, limiting the applicable current and making high yield production challenging. In this study, we pressed a mixture of enriched [ 135 Ba]BaCO3 and fine aluminum (Al) powder to provide a stable target with improved thermal conductivity compared to pure BaCO3 . After 4 h of irradiation with a 16.5 MeV proton beam at 20 μA current, 1.62 ± 0.18 GBq was produced from a 200 mg [ 135 Ba]BaCO3 :Al (1:2, w/w) target. This corresponded to a saturation yield of 11.91 ± 1.31 GBq (or 596 ± 66 MBq/μA). A purification procedure involving initial precipitation, followed by a single composite column containing a layer of TK200 resin and a second layer of branched DGA resin was developed, with 97.1 ± 3.6 % decay corrected 135 La recovery. [ 135 La]LaCl3 was obtained in an effective molar activity of 79.6 ± 25.3 MBq/nmol (DOTA titration), 104.0 ± 40.4 MBq/nmol (DTPA titration) and 186.5 ± 83.8 MBq/nmol (CHX-A″-DTPA titration), and a radionuclidic purity (RNP) of >99.9 % at end of purification, hereby demonstrating a purity suitable for radiopharmaceutical use. Highlights: Production of 135 La (1.6 GBq, EOB) from [ 135 Ba]BaCO3 with a 16.5 MeV cyclotron. Novel cyclotron target consisting of enriched [ 135 Ba]BaCO3 :Al mixture (1:2). Single column with a TK200 resin layer and a DGA resin layer for 135 La purification. Excellent serum stability of 135 La-DOTA and 135 La-CHX-A″-DTPA complexes.